2010
DOI: 10.1088/0964-1726/19/9/094013
|View full text |Cite
|
Sign up to set email alerts
|

Recovery and residual stress of SMA wires and applications for concrete structures

Abstract: In general, NiTi shape memory alloys are used for applications in civil structures. NiTi SMAs show good superelasticity and shape memory effect properties. However, for application of the shape memory effect, it is desirable for SMAs to show a wide temperature hysteresis, especially for civil structures which are exposed to severe environmental conditions. NiTiNb SMAs, in general, show a wider temperature hysteresis than NiTi SMAs and are more applicable for civil structures. This study examines the temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 26 publications
2
34
0
Order By: Relevance
“…The shape memory effect of NiTiNb SMAs has been utilized to actively confine concrete elements [18][19][20][21][22][23][24][25]. NiTiNb SMA spirals were wrapped around concrete cylinders and columns, then heated to activate the shape memory effect.…”
Section: Introductionmentioning
confidence: 99%
“…The shape memory effect of NiTiNb SMAs has been utilized to actively confine concrete elements [18][19][20][21][22][23][24][25]. NiTiNb SMA spirals were wrapped around concrete cylinders and columns, then heated to activate the shape memory effect.…”
Section: Introductionmentioning
confidence: 99%
“…The developed or remaining recovery stress depends on the temperature of the wire and becomes zero when the temperature decreases to M s , where the martensite starts. Furthermore, the recovery and residual stresses depend on the alloy types, such as NiTi or NiTiNb, and the temperature window of the SMA alloys [2,3]. The recovery stress can be used to provide external confinement for reinforced concrete columns [3] or prestress in reinforced concrete beams [4].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the recovery and residual stresses depend on the alloy types, such as NiTi or NiTiNb, and the temperature window of the SMA alloys [2,3]. The recovery stress can be used to provide external confinement for reinforced concrete columns [3] or prestress in reinforced concrete beams [4]. Several previous studies showed that SMA wires were very effective in providing external confinement for concrete [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…As illustrated in Figure 6, the cold-drawn NiTi SMAs show stress-relaxation with decreasing temperature after inducing recovery stress with high temperature (Choi et al, 2010b). For crack-repairing, the high recovery stress would work to close a crack, and, then, after the repairing, the stress would decrease.…”
Section: Discussion and Applicationsmentioning
confidence: 99%
“…Pre-elongated martensitic SMAs with deformation-restraint induce recovery stress by heating up above transformation temperature but lose some level of stress by cooling (see Figure 1(b)); the remaining stress can be used for post-tensioning or prestressing forces. The recover and residual stress highly depends on the alloy composition, manufacturing process, and strain of pre-elongation (Shin & Andrawes, 2010;Choi et al, 2010b;Saleeb et al, 2015a;Saleeb et al, 2015b).…”
Section: Sma Fibers Without End-hooksmentioning
confidence: 99%